Impact of psychoeducation intervention module on parents of children with autism spectrum disorders: A preliminary study - Patra, Suravi (J Neurosci Rural Pract, 2015)
CONTEXT: Parents of children with autism spectrum disorders (ASD) in India face a host of challenges, while seeking care which ranges from unavailability of information to difficulty in availing services. AIMS: To develop a psycho-education intervention module for parents of children with ASD and to study its impact on parent stress and knowledge. SETTINGS AND DESIGN: Child Guidance Clinic Department of Psychiatry, Government Medical College and Hospital, Chandigarh. Interventional study. METHODOLOGY: Parents of children diagnosed with ASD as per Diagnostic and Statistical Manual of Mental Disorders, 4(th) Edition criteria, recruited through consecutive sampling. Total number of 18 participants participated in the two phase study. Phase I included preparation of a parent training module through a four stage process and Phase II was evaluation of impact of the final version of the module on parental stress and knowledge. STATISTICAL ANALYSIS: Wilcoxon Signed-Rank test using SPSS version 17.0. RESULTS: There was an improvement in all the domains of parenting stress and knowledge. Social stress score and total stress score showed significant improvement. CONCLUSIONS: Parent psycho-education intervention module on ASD decreases parenting stress, and improves knowledge about ASD. Psycho-education intervention module is a feasible and acceptable way of parent empowerment.